Effect of drip irrigation on growth and yield of onion (Allium cepa L.) - R C Gupta, H P Sharma, P K Gupta, P Bhasker, R K Singh, (Journal of Spices and Aromatic Crops, 2018)
Drip irrigation is one of the essential, advanced and innovative irrigation methods over surface irrigation. In view of this, an experiment was conducted to study the efficiency of drip irrigation system over surface irrigation in onion during Rabi 2013-14 and 2014-15 and Kharif 2014 and 2015. The results revealed that drip irrigation system performed superior over surface irrigation system in terms of superior plant morphology, yield and quality of bulb. Drip irrigation recorded maximum plant height (66.37 cm & 61.88), number of leaves (9.23 & 8.00) and neck thickness (1.62 cm & 1.30 cm) in both Rabi and Kharif seasons. The bulb equatorial and polar diameter, higher gross yield as well as marketable yield obtained in drip irrigation system. In drip, gross yield and marketable yield increased 18.16% and 24.49%, respectively over surface irrigation method and better water use efficiency and also saved 29.36% and 27.12% water during Rabi and Kharif seasons, respectively.